Sorption isotherms and drying kinetics of grapefruit seeds - doi: 10.4025/actascitechnol.v35i4.13658 - Cantu-Lozano, Denis; Viganó, Juliane; Lassman, Alejandro Alvarado; Vallejo Cantu, Norma Alejandra; Telis-Romero, Javier (Acta Scientiarum. Technology, 2013)
The drying of grapefruit seeds, by-products from grapefruit processing, was studied at 40, 50, 60 and 70Â°C and at three air velocities, 0.6, 1.0 and 1.4 m s-1. Sorption isotherms of grapefruit seeds were obtained at each temperature by the static method using saturated salt solutions. The Henderson model adequately described the sorption isotherms, over the entire temperature range. Drying rates indicated that the drying of grapefruit seeds took place under the falling rate period. Effective moisture diffusivity in grapefruit seeds ranged from 4.36 í— 10-10 to 6.82 í— 10-10 mÂ² s-1. The temperature dependence of the effective diffusivity followed an Arrhenius relationship, and the activation energies were 12.23, 11.29 and 11.79 kJ mol-1 for dried grapefruit seeds under air velocities of 0.6, 1.0 and 1.4 m s-1, respectively. Three thin-layer models were used to predict the drying curves, Page, Lewis, and Henderson-Pabis model. The Page model presented the best fit for all drying air temperatures and velocities studied. Â 